A phase I oncolytic virus trial with vesicular stomatitis virus expressing human interferon beta and tyrosinase related protein 1 administered intratumorally and intravenously in uveal melanoma: safety, efficacy, and T cell responses - Smith, Katherine E. R.; Peng, Kah-Whye; Pulido, Jose S.; Weisbrod, Adam J.; Strand, Carrie A.; Allred, Jacob B.; Newsom, Alysha N.; Zhang, Lianwen; Packiriswamy, Nandakumar; Kottke, Timothy; Tonne, Jason M.; Moore, Madelyn; et al. (Frontiers in Immunology, 2023)
Introduction Metastatic uveal melanoma (MUM) has a poor prognosis and treatment options are limited. These patients do not typically experience durable responses to immune checkpoint inhibitors (ICIs). Oncolytic viruses (OV) represent a novel approach to immunotherapy for patients with MUM. Methods We developed an OV with a Vesicular Stomatitis Virus (VSV) vector modified to express interferon-beta (IFN-β) and Tyrosinase Related Protein 1 (TYRP1) (VSV-IFNβ-TYRP1), and conducted a Phase 1 clinical trial with a 3 + 3 design in patients with MUM. VSV-IFNβ-TYRP1 was injected into a liver metastasis, then administered on the same day as a single intravenous (IV) infusion. The primary objective was safety. Efficacy was a secondary objective. Results 12 patients with previously treated MUM were enrolled. Median follow up was 19.1 months. 4 dose levels (DLs) were evaluated. One patient at DL4 experienced dose limiting toxicities (DLTs), including decreased platelet count (grade 3), increased aspartate aminotransferase (AST), and cytokine release syndrome (CRS). 4 patients had stable disease (SD) and 8 patients had progressive disease (PD). Interferon gamma (IFNγ) ELIspot data showed that more patients developed a T cell response to virus encoded TYRP1 at higher DLs, and a subset of patients also had a response to other melanoma antigens, including gp100, suggesting epitope spreading. 3 of the patients who responded to additional melanoma antigens were next treated with ICIs, and 2 of these patients experienced durable responses. Discussion Our study found that VSV-IFNβ -TYRP1 can be safely administered via intratumoral (IT) and IV routes in a previously treated population of patients with MUM. Although there were no clear objective radiographic responses to VSV-IFNβ-TYRP1, dose-dependent immunogenicity to TYRP1 and other melanoma antigens was seen.